EFEK GAMBIR UNCARIA GAMBIRHUNTER ROXB TERHADAP AKTIVITAS LOKOMOTOR DAN NEUROKOGNITIF PADA TIKUS BETINA MODEL ALZHEIMER - Ulya Uti Fasrini,* Restu Susanti,** Nur Indrawaty Lipoeto* (NEURONA, 2017)
INTRODUCTION LOCOMOTOR ACTIVITY LA DISTURBANCE AND NEUROCOGNITIVE IMPAIRMENT IN ALZHEIMERS DISEASE AD MECHANISM WAS SUGGESTED THROUGH MANY WAYS ONE OF THEM IS THE INDUCTION OF OXIDATIVE STRESS THAT CORRUPTED HIPPOCAMPUS CORTEX